Work Integration on the Family Life of Professional Working Mothers - Pajarillo Agustin, DPA, Chona (International Journal of Psychosocial Rehabilitation, 2020)
The influx of the industrial revolution created many changes in society, in the family, and in family life. The advent of industrialization, coupled with the global economic and social development, created rapid changes in the cultural setting. Many activities traditionally performed by the family and the woman in the home have been inevitably superseded by the introduction of labor-saving machines or technologically aided tools, thus providing the woman with time to engage in full-time or part-time jobs outside the home. This study focuses on the professional working mothers in a rural setting, specifically seeking to identify their personal and work profile and describe their family life as well as the effects of their employment and/or the practice of their profession on the different aspects of their family life. A sample of 180 professional working mothers who have at least one or two children and have resided in the place for at least three years were taken as the primary sources of data for the study. A descriptive normative method of research was used. Utilizing the data gathered from the respondents, the results of this study showed that the respondents’ careers beneficially affect their family lives in all aspects in the sense that the careers serve as a deciding factor for them to plan their families. Considering the needs of time, having working mothers leave their homes every day to spend the day at their workplace is but a common and natural occurrence. This study proved that there are advantages and benefits being derived from having professional wives in terms of the different dimensions mentioned in this study. However, it is important for the professional working mothers to grow professionally and personally by ensuring graduate courses and possessing the skill of proper time and resource management to promote smooth family relations.